Current Perspectives on the Extraction, Isolation, and Identification of Fats and Fatty Acids Using Conventional and Green Methods - Ytaiara Lima-Pereira; Esther Maria Oliveira de Souza; David Silva dos Reis; Ian Gardel Carvalho Barcellos-Silva; Karine Sayuri Lima Miki; Valdir F. Veiga-Júnior; Barbara Elisabeth Teixeira-Costa (Separations)
The global demand for oils and lipids, particularly those derived from vegetable sources with high polyunsaturated fatty acid content, has posed significant challenges for the food industry. This trend is largely driven by growing consumer awareness of health and nutrition. To meet this demand, it is essential to not only identify richer sources of lipids but also develop efficient, sustainable, and environmentally friendly methods for their extraction, isolation, and characterization. In this context, the present work provides a comprehensive review of current perspectives on the extraction, isolation, and identification of lipids and fatty acids, comparing conventional and green methodologies for food applications. Ideally, analytical and processing methodologies for obtaining food-grade materials should prioritize low energy consumption, minimal or no use of hazardous substances, and the generation of non-polluting residues, thereby safeguarding both human health and the environment. In recent years, green extraction techniques have emerged as promising alternatives to conventional methods, offering partial or complete replacements, such as ultrasound-assisted extraction, microwave-assisted extraction, supercritical and subcritical fluid extraction, and others. However, significant advancements are still required to fully address these concerns. Techniques such as chromatography and spectrometry play pivotal roles in the isolation and identification process, especially gas chromatography coupled with mass spectrometry or with flame ionization detectors; while separating individual fatty acids based on their chain length and degree of unsaturation, reversed-phase high-performance liquid chromatography (HPLC) is quite a helpful approach. Furthermore, the isolation and structural elucidation of fatty acids are critical steps in ensuring the nutritional quality and commercial viability of lipid products.